2021
DOI: 10.1038/s41598-021-02933-5
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical approach on the ability of functionalized gold nanoparticles for detection of Cd2+

Abstract: Cadmium (Cd) as a toxic element that is widely present in water, soil, and air has important effects on human health, therefore proposing an accurate and selective method for detection of this element is of importance. In this article, by employing full atomistic molecular dynamics (MD) simulations and density functional theory dispersion corrected (DFT-D3) calculations, the effects of 6-mercaptonicotinic acid (MNA) and l-cysteine (CYS) on the stability of gold nanoparticles (AuNPs) and their sensitivity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(67 reference statements)
2
3
0
Order By: Relevance
“…Regarding Cer, recognized as a significant factor in inflammation, 22 prior COVID-19 studies have indicated elevated Cer levels, contingent on the molecular species. 17,23,24 However, in our investigation, both the COVID and non-COVID groups exhibited decreased Cer levels, which remained consistently reduced regardless of disease severity or time-course, mirroring the pattern observed with S1P. This reduced Cer level may be attributed to elevated levels of its downstream sphingolipid metabolites, including Sph, Cer1P, HexCer, and LacCer (Figure 6).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Regarding Cer, recognized as a significant factor in inflammation, 22 prior COVID-19 studies have indicated elevated Cer levels, contingent on the molecular species. 17,23,24 However, in our investigation, both the COVID and non-COVID groups exhibited decreased Cer levels, which remained consistently reduced regardless of disease severity or time-course, mirroring the pattern observed with S1P. This reduced Cer level may be attributed to elevated levels of its downstream sphingolipid metabolites, including Sph, Cer1P, HexCer, and LacCer (Figure 6).…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, a notable decrease was evident in the severe group at multiple time points (Figure 3B). Regarding Cer, recognized as a significant factor in inflammation, 22 prior COVID‐19 studies have indicated elevated Cer levels, contingent on the molecular species 17,23,24 . However, in our investigation, both the COVID and non‐COVID groups exhibited decreased Cer levels, which remained consistently reduced regardless of disease severity or time‐course, mirroring the pattern observed with S1P.…”
Section: Discussionsupporting
confidence: 62%
“…Heavy metal ions as the main environmental contaminants in water systems cause great harm to human beings and different species of organisms throughout the world 1‐3 . Among these heavy metal ions, cadmium ions are highly toxic to human beings and lead to serious damage to the nervous system, kidney and liver, causing metabolic disorders and other related diseases 4‐6 . Cd 2+ is a priority pollutant and tolerable Cd 2+ concentrations in water are limited as 27 nmol L −1 due to the strong toxic role of cadmium ions 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Among these heavy metal ions, cadmium ions are highly toxic to human beings and lead to serious damage to the nervous system, kidney and liver, causing metabolic disorders and other related diseases. [4][5][6] Cd 2+ is a priority pollutant and tolerable Cd 2+ concentrations in water are limited as 27 nmol L −1 due to the strong toxic role of cadmium ions. 7,8 However, cadmium ions may be discarded to environments with living organisms from fossil fuel combustion, phosphate fertilizer and battery industries.…”
Section: Introductionmentioning
confidence: 99%
“…NPs are very reactive due to the high surface-volume ratio, and tend to precipitate to minimize the surface tension in the colloidal suspension. Therefore, to ensure their colloidal stability, NPs are coated with organic molecules -surfactants- which provide electrostatic, steric or a mixture of both stabilization to NP’s surface 6 8 . They are present in the synthetic mixture from which NPs are produced and play a key role in regulating nucleation and growth processes.…”
Section: Introductionmentioning
confidence: 99%